Genotype-by-environment interaction and selection of superior Physalis peruviana L. genotypes (2023)
Cape gooseberry (Physalis peruviana L.) productivity in Colombia can be increased by developing high-yielding and adaptable varieties identified in multi-environment trials. In this study, the genotype-by-environment interaction (G×E) for fruit yield and fruit weight of 13 cape gooseberry genotypes at seven locations was evaluated using a randomized complete block design. G×E interaction was significant for yield and fruit weight, suggesting a differential response of genotypes across environments. Through the AMMI analysis, similar and contrasting environments were identified, as well as the genotypes that contributed the most to the G×E interaction. Genotypes I, B, D, and H were the high yielding, ranging from 25.2 to 27.3 t ha-1, so they could be recommended for commercial cultivation. Genotypes B and D was stable in yield and widely adapted; while the genotypes I and H showed a specific adaptation for yield and exhibited heavier fruits. Genotype R1 exhibited the greater fruit weight in most locations except Ipiales but showed low fruit yield. The suitable locations for the cultivation of cape gooseberry were Pasto, Puerres, and Ipiales since they presented the highest yields and fruit weight.